Tongxieyaofang Decotion Alleviates IBS by Modulating CHRM3 and Gut Barrier - Feng T; Zhou Y; Lv B; Cai L (Dove Medical Press, 2024)
Tongfei Feng,1- 3,* Yanlin Zhou,1,3,* Bin Lv,1,3 Lijun Cai1,3 1Department of Gastroenterology, The First Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310003, People's Republic of China; 2The First Clinical College of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310053, People's Republic of China; 3Key Laboratory of Digestive Pathophysiology of Zhejiang Province, The First Affiliated Hospital of Zhejiang Chinese Medical University, Zhejiang Chinese Medical University, Hubin Campus, Hangzhou, 310006, People's Republic of China*These authors contributed equally to this workCorrespondence: Lijun Cai; Bin Lv, Department of Gastroenterology, The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine), Hangzhou, Zhejiang, 310053, People's Republic of China, Tel +86-571-86613545, Fax +86-571-87073763, Email 20051018@zcmu.edu.cn; lvbin@medmail.com.cnPurpose: Through network pharmacology combined with molecular docking and in vivo validation, the study examines the unexplored molecular mechanisms of Tongxieyaofang (TXYF) in the treatment of irritable bowel syndrome (IBS). In particular, the potential pharmacological mechanism of TXYF alleviating IBS by regulating CHRM3 and intestinal barrier has not been studied.Patients and Methods: LC-MS technique and TCMSP database were used in combination to identify the potential effective components and target sites of TXYF. Potential targets for IBS were obtained from Genecards and OMIM databases. PPI and cytoHub analysis for targets. Molecular docking was used to validate the binding energy of effective components with related targets and for visualization. GO and KEGG analysis were employed to identify target functions and signaling pathways. In the in vivo validation, wrap restraint stress-induced IBS model was employed to verify the change for cytoHub genes and CHRM3 expression. Furthermore, inflammatory changes of colon were observed by HE staining. The changes of Ach were verified by ELISA. IHC and WB validated CHRM3 and GNAQ/PLC/MLCK channel variations. AB-PAS test and WB test confirmed the protection of TXYF on gut barrier. The NF-κB/MLCK pathway was also verified.Results: In TXYF decoction, LC-MS identified 559 chemical components, with 23 remaining effective components after screening in TCMSP. KEGG analysis indicated that calcium plays a crucial role in TXYF treated for IBS. Molecular docking validated the binding capacity of the effective components Naringenin and Nobiletin with cytoHub-gene and CHRM3. In vivo validation demonstrated that TXYF inhibits the activation of Ach and CHRM3 in IBS, and inhibits for the GNAQ/PLC/MLCK axis. Additionally, TXYF downregulates TNF-α, MMP9, and NF-κB/MLCK, while modulating goblet cell secretion to protect gut barrier.Conclusion: TXYF inhibits Ach and CHRM3 expression, regulating the relaxation of intestinal smooth muscle via GNAQ/PLC/MLCK. Additionally, TXYF inhibits NF-κB/MLCK activated and goblet cell secretion to protect gut barrier. Keywords: irritable bowel syndrome, tongxieyaofang decoction, Ach, CHRM3, GNAQ/PCL/MLCK, gut barrier